2018
DOI: 10.1136/bmj.k934
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake in relation to non-fatal and fatal coronary heart disease and stroke: EPIC-CVD case-cohort study

Abstract: ObjectiveTo investigate the association between alcohol consumption (at baseline and over lifetime) and non-fatal and fatal coronary heart disease (CHD) and stroke.DesignMulticentre case-cohort study.SettingA study of cardiovascular disease (CVD) determinants within the European Prospective Investigation into Cancer and nutrition cohort (EPIC-CVD) from eight European countries.Participants32 549 participants without baseline CVD, comprised of incident CVD cases and a subcohort for comparison.Main outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 36 publications
2
70
2
Order By: Relevance
“…37 The EPIC-CVD case cohort study also found a clear trend between increased alcohol consumption and stroke risk. 38 While Western vegetarians use ample amounts of garlic and other allium vegetables, Asian Buddhist vegetarians avoid these vegetables. Allium vegetables are major sources of alliin/allicin, known to inhibit platelet function and induce bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…37 The EPIC-CVD case cohort study also found a clear trend between increased alcohol consumption and stroke risk. 38 While Western vegetarians use ample amounts of garlic and other allium vegetables, Asian Buddhist vegetarians avoid these vegetables. Allium vegetables are major sources of alliin/allicin, known to inhibit platelet function and induce bleeding.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In addition, the mechanisms underlying the association between alcohol and cognitive aging remain unclear. 5 6 7 Non-moderate alcohol consumption is associated with a higher risk of cardiometabolic disease, 1 13 14 15 which is itself associated with a higher risk of dementia, 4 16 suggesting a potential role of these diseases in the association between alcohol consumption and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been associated with over 200 health conditions including neuropsychiatric conditions, liver cirrhosis, several cancers, hypertensive heart disease, fetal alcohol syndrome, and infectious diseases [ 1 ]. Moderate alcohol intake was found to be inversely associated with the risk of type 2 diabetes [ 2 ] and heterogeneous associations were observed for cardiovascular disease subtypes, with an inverse association with coronary heart disease, and a positive association with stroke [ 3 , 4 ]. Each year, alcohol causes approximately 3.3 million deaths, i.e., one in every 20 deaths in the world [ 1 ].…”
Section: Introductionmentioning
confidence: 99%